PENGARUH STIMULAN AKAR DAN MEDIA TANAM PADA PERTUMBUHAN SETEK PUCUK PANGAL (Baccaurea bracteata Muell.Arg.) - Mentari, F; Wulandari, Reine Suci (Universitas Tanjungpura, 2019)
Pangal (Baccaurea bracteata Muell.Arg.) is a flowering plant belonging to the Phylanhace tribe know as fruit and wood producer. The pangal plant is native to debt, but its existence is diminishing now. Therefore, it is necessary to procure seedlings for forest restoration with cuttings. The purpose of this study was to obtain root stimulants and planting medium suitable for the growth of pangan shoot cuttings. This experiment used a (split plot) design with a completely randomized design (CRD). The main plot factor was the planting medium with two levels of factor (cocopeat (M1) and cocopeat with husk charcoal (M2)). The subplot factor consists of three levels of factor (control (Z1), rootone-F (Z2) and wood vinegar (Z3)). Each treatment was replicated five times to obtain 30 units of treatments. The result showed the highest percentage of life (60%) was obtained by in cuttings that were treated with rootone-F and were planted in cocopeat medium and rice huck mixture. After being tested statistically, the effect of planting media (cocopeat or mixture of cocopeat and husk charcoal) and root stimulants (without root stimulants, rootone F or wood vinegar) was not significant to primary root length, primary root number, secondary root number, number of leaves and shoot length. Keyword: Baccaurea bracteata, husk charcoal wood vinegar, rootone-F.